2018
DOI: 10.1055/s-0038-1667145
|View full text |Cite
|
Sign up to set email alerts
|

Survival following Multimodality Treatment Including Surgery for Stage IA–IIIB Small-Cell Lung Cancer

Abstract: Multimodality treatment including surgery was safe and led to considerable survival. R0 resection was the only factor extending survival. It could be achieved in most patients and was associated with a low risk of locoregional relapse. Prospective randomized controlled studies are needed to define best practice in stage IA-IIIB SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A single-center study by Weckler, B. C. et al retrospectively enrolled 47 patients of SCLC with stage IA-IIIB who underwent combined treatment including surgery (including 6 stage T4 patients), resulting in a postoperative 30-day mortality rate of 0% and good long-term survival with a median overall survival of 56 months. His study evaluated that R0 resection was the only factor influencing long-term survival [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single-center study by Weckler, B. C. et al retrospectively enrolled 47 patients of SCLC with stage IA-IIIB who underwent combined treatment including surgery (including 6 stage T4 patients), resulting in a postoperative 30-day mortality rate of 0% and good long-term survival with a median overall survival of 56 months. His study evaluated that R0 resection was the only factor influencing long-term survival [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, lobe resection was reported to be associated with a longer OS than other types of surgery ( 34 , 35 ). Zhang et al indicated that the combined components of NSCLC would affect the OS ( 12 ), while Weckler BC suggests that complete resection was the only predictor of OS ( 36 ). However, in patients with NSCLC, nerve invasion or vascular invasion have also influenced the OS ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy, including chemotherapy, radiotherapy, and immunotherapy, has been widely accepted for the treatment of SCLC. Although the current National Comprehensive Cancer Network (NCCN) guidelines only recommend surgery for patients with clinical stages I-IIA SCLC (6), many studies have also found that patients with clinical stages II-III SCLC can also benefit from surgery (7)(8)(9)(10)(11)(12)(13). In addition, although more advanced diagnostic methods are now used for the diagnosis and classification of SCLC, the selection of surgical candidates for SCLC is still arbitrary.…”
Section: Introductionmentioning
confidence: 99%